Novel Approach to Selectively Functionalized Derivatives of Sucrose - Kowalski, Michał; Cmoch, Piotr; Jarosz, Sławomir (Synlett, 2014)
New synthetic routes to complex sucrose derivatives are presented. They are based on a highly selective silylation of the hydroxyl group at the C6′ position (‘fructose end’) in 2,3,3′,4,4′-penta-O-benzylsucrose followed by functionalization of the remaining (C-1′,6) positions. One of these synthons was used as a chiral platform for the construction of aza-macrocyclic systems.
Keywords: sucrose; protecting groups; regioselectivity; phase-transfer catalysis; macrocycles